THE DWELLING OF THE RURAL TEACHER IN GALICIA (THE END OF XLX TH – 30S OF THE XXTH CENTURY) - Баран, О. Я. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The dwelling of the galician rural teacher at the end of XlX th – 30s of the XXth century is analized in the article. So peculiarities of planing and interior of the dwelling, houshold buildings on the area of the yard. To the thought of the author, europian fashionable tendencies and traditions of the folk architecture are combined in the teacher’s dwelling.